Fracture Failure Analysis of Hydraulic Pump Drive Shaft - Liu Canjie; Lü Pangong; Dou Xiao Peng; Ma Chengtian; Wang Dongfei; Zhang Hao (Jixie chuandong)
A domestic hydraulic pump drive shaft fracture occurred during the experimental verification.The analysis of working conditions,strength safety factor,finite element analysis of work stress,macro fracture inspection,micro topography,microstructure,chemical composition,material hardness of the drive shaft show that the reason for the failure is that the fillet design at the stepped shaft is too small and the heat treatment does not meet the requirements. The design and process optimization route are given,the foundation for improving the service of the drive shaft is laied.